Biofilm formation by Campylobacter jejuni in controlled mixed-microbial populations : a thesis presented in partial fulfillment of the requirements for the degree of Master of Technology in Food Technology at Massey University, Palmerston North, New Zealand - Teh, Koon Hoong (Massey University, 2008)
Poultry meat consumption in New Zealand has been increasing since 1975 with the highest peak reported in 2006. The total poultry meat consumption was 36.5 kg per capita in the year ending September 2006. Consumption of contaminated food with raw poultry can lead to campylobacteriosis, which is a food-borne disease that causes gastroenteritis in humans and it is a major problem in New Zealand. There were 12,776 reported cases of campylobacteriosis in 2007, which accounts for 65.9% of the overall notified diseases. Campylobacteriosis can lead to Guillain-Barré syndrome in some patients, an autoimmune disorder of the peripheral nervous system. Campylobacteriosis is caused by consumption of either Campylobacter jejuni or Campylobacter coli. Campylobacter spp. have been found in commercially raised poultry being infected predominantly by C. jejuni. C. jejuni has been found associated with biofilms of other bacterial species in the watering supplies and plumbing systems of animal husbandry facilities and animalprocessing plants. A biofilm is an assemblage of microbial cells that is associated with a surface and the cells are enclosed in a matrix of polysaccharides, which provides a survival advantage to the bacteria in the film. In this study, the ability to form biofilm was measured in a laboratory assay using microtitre plates. C. jejuni strains in monoculture were shown to attach to the abiotic surface and form biofilms to various degrees, thus potentially enhancing their survivability in the poultry environment. C. jejuni was also shown to have the ability to attach and survive in mixed-microbial populations. Biofilm formation may play a role in the epidemiology of C. jejuni infections. Enterococcus faecalis and Staphylococcus simulans may play a role in the biofilm formation in the poultry environment as both of these microorganisms were able to form, and harbour C. jejuni in their biofilms. Pseudomonas aeruginosa seemed to inhibit biofilm formation and C. jejuni in the mixed-microbial population. Further studies are required to establish control measures against the formation of biofilms containing C. jejuni in poultry processing plants and farms in New Zealand to reduce the reservoir of contamination and thus reduce the incidence of campylobacteriosis.
Keywords: Campylobacter jejuni; Biofilm; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290101 Fermentation, biotechnology and industrial microbiology